Exploring experiential learning with immersive virtual reality as a framework for taeching delivery in architectural design studio - Abdul Ghani, Annisa Ummihusna (2022)
Architects’ basic architectural understandings are derived from their personal experience gained since childhood. Thereby, a formal architecture curriculum cannot be comprehended merely from a classroom or studio; it requires students to observe and participate in outdoor architectural settings. Young designers, therefore, may struggle in the early stages of an architectural programme as most begin their education with little experience in perceiving and understanding spaces. Each of them may have a varied level of spatial understanding experience that influenced their approach to the design process. For this reason, site visit activities have been a key component in architecture education to provide students with experiential learning experiences. Nevertheless, challenges in managing site visits and limitations as the Covid-19 pandemic have hampered the overall learning experience. Therefore, this study aimed to explore how experiential learning (EL) with immersive virtual reality (IVR) as a learning tool can enhance first-year architecture students’ spatial understanding experience during the architecture design process. An IVR simulation named Architectural Spatial Experience Simulation (ASES) which can actively enrich spatial understanding was designed, developed, and implemented in a first-year architecture design studio. Action research was employed by the practitionerresearcher in an architecture design studio environment for two consecutive semesters involving ten students undertaking the first-year design studio course in each cohort. The two cycles of action research involved multiple data collection strategies and instruments, such as desk reviews, observation, reflective memos, journals and textual records of design work. Data collected were then analysed using qualitative descriptive analysis and thematic analysis. The findings indicate that EL theory with IVR is recognised as a promising approach to support spatial understanding experiences among first-year architecture students during the architecture design process. ASES was established to enhance the participants’ spatial understanding and encourage changes in their approach to learning from surface to deep learning. IVR with EL was found to provide visual, experiential, versatility, and emotional attributes, thus enhancing the students’ spatial understanding experience. The Experiential with IVR Architecture Design Learning (EVADL) framework was formulated in guiding the integrated application of EL with IVR during the design process and was recognised to provide structure in the architecture design studio learning activities. This study has established empirical exploration and enhanced the theoretical understanding of experiential learning in the architecture design education context. In practice, the study has developed ASES which can serve as an active tool in replacing the concrete experience in EL and resolving the difficulties of conducting site visit activities. ASES able to enrich students’ spatial understanding experience and encourages a deep learning approach. The EVADL framework can serve as a guideline for ILT intervention in architecture design studios for educators during the planning stage of the studio course. Future studies may be implemented on a broader scale to validate the appropriateness of the applications in different architecture schools. The potential for collaborative action research to be performed among educators in other higher institutions that might have similar interests or concerns on first-year architecture students.